ä¸¹æˆŽå¸ƒæ‹‰å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯æ•™è‚²ä¸“ä¸š2020å’Œ2021å±ŠéžåŽæ—å¦ ç”Ÿé˜…è¯»ç†è§£çš„å›°éš¾åˆ†æž - Marandani, Fira; Ina, Ina; Veronica, Tjen (Universitas Tanjungpura, 2023)
Reading class is an crucial component of Chinese language education, and many individuals, particulary non-Chinese students lacking a foundation in the language, find it challeging due to the difficulties encountered during the learning process. To identify the reasons for these challenges, the author conducted a research study among non-Chinese students majoring in Chinese language educatin at the School of Teacher Education, Tanjung Pura University in 2020 and 2021. The purpose of this research was to gain insight into why nonChinese students in the 2020 and 2021 cohorts of the Teacher Education College at Tanjung Pura University faced difficulties in their reading courses and to learn strategies to overcome these challenges. This study employed quantitative data analysis methods, utilizing a questionnaire survey and test question. Based on the finding of this research, the author concluded that the primary difficulties in comprehending Chinese reading texts stem from challenges in understanding the meanings of new words, a lack of foundational knowledge, complex grammar, and difficulty in grasping the content of the readings. The results of this study demonstrate that the reading comprehension skills of non-Chinese students in the 2020 and 2021 Chinese language programs remain underdeveloped, emphasizing the need for continued improvement in their ability to comprehend Chinese texts